An Amish baby for Christmas [large type] - Chapman, Vannetta (Chapman, Vannetta. Indiana Amish brides., 2021)
"In danger of losing her farm after her husband's death, Abigail Yutzy needs help--even if she can't afford it. At her bishop's insistence, property manager Thomas Albrecht pitches in to aid the pregnant widow. With his troubled past and her shattered heart, their arrangement must stay business only. But their uneasy holiday alliance might just heal both their hearts."--Back cover.